Maintenance of Increased Mouth Opening in Oral Submucous Fibrosis Patient Treated with Nasolabial Flap Technique - Milind Naphade; Bhushan Bhagat; Dwarkadas Adwani; Ranjit Mandwe (Hindawi Limited, 2014)
Oral submucous fibrosis (OSMF) is an insidious chronic disease affecting any part of the oral cavity and sometimes the pharynx with epithelial atrophy leading to stiffness of the oral mucosa, causing trismus and inability to eat. However, a more serious complication of this disease is the risk of the development of oral carcinoma. A case of OSMF reported with initial interincisal mouth opening; 8 mm which was treated surgically with nasolabial flap technique followed by active mouth opening exercises for 6 months with Hister's jaw exerciser. The patient could maintain mouth opening of 32 mm at the end of 18-months followup. The patient was observed closely for any malignant changes in the oral cavity.